Peer editing: a strategic source in EFL students’ writing process - Díaz Galvis, Nubia Mercedes (Colombian Applied Linguistics Journal, 2010)
This article reports on a research project focused on peer editing as a pedagogical tool to promote collaborative assessment in the EFL writing process. With teachers overstretched in the Bogotá public school system, a method needed to be found that would allow students to receive much needed feedback without overtaxing the teachers` resources. Peer editing, a phenomenon that often occurs naturally within the classroom, was therefore systematically implemented as a solution to the stated problem. The main aims of this study, conducted with a group of ninth grade student at a public school in Bogotá, were to determine the role of peer editing in the writing process and to characterize the relationships built when students corrected each others writings. The instruments used for collecting data were field notes, video recordings and students’ artifacts. The results showed that when students were engaged in peer editing sessions they created zones of proximal development in which high achiever students provided linguistic scaffolding and empowered low achievers. It was also found that students used thinking strategies such as noticing and explaining when they identified errors related to the formal aspects of the language.